Mosby's pocket dictionary of medicine, nursing & health professions - O'Tool, Marie T. (St. Louis, Missouri : Elsevier, 2017)
This dictionary focuses on nursing and health science terminology and offers over 56,600 authoritative definitions of diseases, procedures, equipment, and drugs.--
Keywords: Medicine -- Dictionaries; Nursing -- Dictionaries; Health -- Dictionaries; Health; Medicine; Nursing; Dictionaries